Application of Delphi method to identify sustainable university assessment criteria for Vietnam - Hang, Tran Thi Minh; Huong, Tran Thi; Son, Pham Hung; Khai, Nguyen Manh (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 1DO - 10.25073/2588-1094/vnuees.4790, 2023)
Abstract: This study was conducted to determine the criteria for evaluating sustainable universities for Vietnam. The Delphi method is used to collect opinions of experts from the field of environment and sustainable development on some proposed criteria. The results of the first round of Delphi were synthesized and analyzed according to KAMET principles. A set of proposed criteria have been identified and selected. The Kendall coefficient, calculated from the Delphi round 2 questionnaire, is 0.52, showing a strong consensus and high level of confidence of experts on the four groups of sustainable university evaluation criteria for Vietnam, including: Research training and participation in extracurricular activities; Operation; Governance and policy; Community involvement and social responsibility. The research results provide the foundation for a set of criteria to evaluate sustainable universities for Vietnam.